Antimicrobial, anti-biofilm, and anti-proliferative activities of lipopeptide biosurfactant produced by Acinetobacter junii B6. (January 2020) - Ohadi, Mandana; Forootanfar, Hamid; Dehghannoudeh, Gholamreza; Eslaminejad, Touba; Ameri, Atefeh; Shakibaie, Mojtaba; Adeli-Sardou, Mahboubeh
Abstract: Lipopeptide biosurfactants (LPBs) are amphiphilic compounds produced by microorganisms exhibiting various biological activities. The main aim of the present study was to assess the in vitro antimicrobial, anti-biofilm, and cytotoxic effects of LPB produced by Acinetobacter junii ( Aj L). We determined Aj L minimum inhibitory concentration (MIC) against both Gram-positive and Gram-negative bacteria as well as two fungal strains. Also, the anti-biofilm activity of Aj L against the biofilm produced by clinically isolated bacterial strains was investigated. The Aj L non-selectively showed activity against both Gram-positive and Gram-negative bacterial strains. The obtained results of the present study exhibited that the Aj L in concentrations nearly below critical micelle concentration (CMC) has an effective antibacterial activity. It was found that the MIC values of Aj L were lower than standard antifungal and it exhibited nearly 100% inhibition against Candida utilis. The attained results of the biofilm formation revealed that Aj L disrupted the biofilm of Proteus mirabilis, Staphylococcus aureus, and Pseudomonas aeruginosa at 1250 μg/ml and 2500 μg/ml concentrations. The attained results of cytotoxic effect (determined by WST-1 assay) of the Aj L revealed IC50 of 7.8 ± 0.4 mg/ml, 2.4 ± 0.5 mg/ml, and 5.7 ± 0.1 mg/ml, against U87, KB, and HUVEC cell lines, respectively. The results indicated that Aj L has a potential application in the relatively new field of biomedicine. Highlights: The produced lipopeptide biosurfactant of A. junii B6 ( Aj L) showed MIC of 5 μg/ml. The Aj L disrupted the biofilm formed by clinical isolates of three bacterial pathogens. The calculated IC50 of Aj L against HUVEC cell line was found to be 7.8 ± 0.4 mg/ml.